Passive sampler derived polychlorinated biphenyls (PCBs) in indoor and outdoor air in Bursa, Turkey: Levels and an assessment of human exposure via inhalation - Sari, Mehmet Ferhat; Esen, Fatma; Del Aguila, Daniel Alejandro Cordova; Kurt Karakuş, Perihan Binnur (Turkish Natl Committee Air Pollution Res & Control-Tuncap, 2020)
Although polychlorinated biphenyls (PCBs) were banned several years ago, they can still be measured in the environment, especially in indoors, where their concentrations tend to be higher than outdoors in some cases. The current study reports the results of a study conducted to determine concentrations of a total of 40 PCBs congeners in the living rooms and kitchens of eight different houses, and in the outdoor air of three houses during summer and autumn in Bursa in 2014. The province of Bursa, having eighteen of organized industrial zones, indoor air pollution is of great importance. The average concentration of Sigma(40)PCBs in living rooms and the kitchen were 604 +/- 210 pg/m(3) and 639 +/- 2514 pg/m(3) during summer, respectively; while concentrations in autumn were 362 +/- 167 pg/m(3) and 309 +/- 93 pg/m(3), respectively. The average Sigma(40)PCBs outdoor concentrations were 303 +/- 183 pg/m(3) and 41 +/- 23 pg/m(3) for summer and autumn, respectively. The Sigma(40)PCBs concentrations in summer were almost two times higher than in autumn for indoor environment. The predominant PCB homologs in indoor samples were penta- (40%), tetra- (23%) and tri-CBs (17%) while they were penta- (37%) and tetra-CBs (22%) for outdoor samples. The results of the study indicated the presence of intentionally and unintentionally produced PCBs. The I/O ratios suggested the indoor sites as the most important PCBs source than outdoor sites. Finally, the measured PCB concentrations did not represent a cancer risk for human health for exposure via inhalation in all sampling points.
Keywords: Indoor air; Outdoor air; PCBs; Health effect; Sources identification; Air quality